Environmental literacy model in organic waste processing based on eco enzyme - Fiddien, Himma Aliyah; Anwar, Rully Khairul; Khadijah, Ute Lies Siti (Perpustakaan Universitas Gadjah Mada, 2025)
Introduction. Community Reading Space or Taman bacaan masyarakat (TBM) can play a significant role in environmental literacy through literacy programs offered to residents. This study aims to examine the role and stages of environmental literacy in organic waste processing based on eco enzyme and to describe the program development strategy implemented. Data Collection Methods. This study employed a qualitative method with a case study approach at Rumah Baca Jatmika. Data collection was conducted through observations, interviews, and document studies. Four informants and one expert in environmental literacy were selected using purposive sampling. Data Analysis. Data analysis in this study was conducted through data reduction, data presentation, and conclusion drawing. Results and Discussion. Rumah Baca Jatmika as an agent of change involved in environmental literacy created an eco enzyme based organic waste processing program. The model developed includes stages that the approach, planning, preparation, implementation, evaluation and motivation, and development stages. The program development strategy is carried out by utilizing personal closeness between TBM managers to hold joint activities and provide mutual benefits. Conclusion and Recommendations. The implementation of the eco enzyme production program has a positive impact on changing the attitudes of participants who have begun to sort waste at the household level. The role of volunteers is highly needed to support the program.